THE EFFECT OF CORPORATE GOVERNANCE STRUCTURES, ENVIRONMENTAL PERFORMANCE, AND MEDIA COVERAGES TO CARBON EMISSIONS DISCLOSURE - Ardillah, Kenny; Rusli, Yohanes Mardinata (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract ” Companies are currently required to be more transparent and accountable in disclosing environmental information. One of them is the disclosure of carbon emissions which are part of the form of environmental disclosure carried out voluntarily by the company. The purpose of this research is to prove the positive effect of institutional ownership, independent commissioners, environmental performance, and media coverage to carbon emissions disclosure. The extent of carbon emission disclosure was measured by carbon disclosure information index that provided by the Carbon Disclosure Project. The author used mining companies listed on the Indonesia Stock Exchange for 2015 – 2019 as research sample that was selected by using purposive sampling method. The analytical method used in this research was multiple regression analysis. This research showed that independent board of commissioners, environmental performance, and media coverage had positive effect on carbon emissions disclosure. On the other hand, the institutional ownership had negative effect to carbon emissions disclosure. From this result of research, the companies can increase sensitivity or attention to emission carbon disclosure, especially for corporations that have direct contact and impact on society and the environment in surroundings. Keywords: Institutional Ownership; Independent Commissioners; Environmental Performance; Media Coverage; Carbon Emissions Disclosure